Characterization of the first bovine gammaherpesvirus 4 strain isolated from an aborted bovine fetus in Argentina - Romeo, Florencia (2020)
Bovine herpesvirus 4 (BoHV-4) is increasingly believed to be responsible for several disorders of the bovine reproductive tract. The first characterization of BoHV-4 in Argentina was from samples from an aborted fetus. Argentinean isolates are highly diverse and are phylogenetically grouped in three genotypes. In this study, we describe the isolation of BoHV-4 from a bovine fetus with a gestational age of 8 months and without macroscopic lesions. Genetic analyses revealed that the isolated strain belongs to genotype 2. This is the first report on the presence of infectious BoHV-4 in tissues from an aborted bovine fetus